Lipid Lowering and Hepatoprotective Activity of Premna Tomentosa Leaf Extract (EPT) against Alcohol Induced Toxicity in Rats: Life Sciences-Anatomy For Better Medical Therapy - Dr. T. Gomathi Priyadharsini; Dr. M. Kavimani (International Journal of Life Science and Pharma Research, 2022)
The present study aims to determine the hepatoprotective and lipid lowering property of ethanolic leaf extract of Premna tomentosa (EPT) in alcohol induced hepatotoxicity. Chronic ethanol consumption is a significant danger factor in deciding liver disorders and other metabolic conditions through various mechanisms, including the regulation of the lipid metabolism. Medicinal plants are accepted to be a significant wellspring of new chemical substances with expected remedial impacts. Premna tomentosa (Verbenaceae) is a popular medicinal plant used extensively for the treatment of various ailments widely used in liver disorders. In the present research study, the male albino Wister rats were grouped (I-V) each consisting of 6 animals. In-vivo administration of 40 % ethanol (1 ml/100 gm b w/day) for 60 days resulted in a significant elevation in Total cholesterol, Triglycerides, LDL, and VLDL levels whereas the levels of HDL was found to be decreased when compared with the control rats. Liver tissues disclose central vein and sinusoidal capillary dilation, interface hepatitis, cytoplasmic vacuolization and mononuclear cell infiltration which confirms the intensity of liver damage due to chronic alcohol ingestion. Simultaneous EPT supplementation (500mg/kg and 750 mg/kg bw) to alcohol -intoxicated rats, reduced the levels of Total cholesterol, triglycerides, and lipoproteins consequential as analogized with the unsupplemented alcohol- treated rats. Liver of rats pre-treated with ethanolic extract of Premna tomentosa (500 mg and 750 mg) manifest reduced formation of interface hepatitis, vascular congestion, and fatty degeneration and exhibits more hepatoprotection compared with the rats pre-treated in Liv 52. The blood parameters were amplified by the histopathological perusal of the liver. The lipid -lowering property by the derivatives of cinnamic acid showed anticholesteremic activity. The results confirm the Hepatoprotective and lipid -lowering ability of Premna tomentosa in alcohol-treated rats.